Ri'e Hikun Liman Wanan Communication Media with Rera Wulan Tana Ekan - Yosef Demon; Veronika Genua (Randwick International of Education and Linguistics Science Journal, 2020)
The traditional people's belief in God as the Supreme Cause of the universe can be expressed in various ways. The methods used are the inner representation of traditional society of the existence of a God who created the heavens and the earth. The Lamaholot people refer to God as Rera Wulan Tana Ekan 'Creator of Heaven and Earth' in a cultural perspective. Rera Wulan Tana Ekan in the perspective of Lamaholot culture is the Highest Being who is believed to have perfect abilities such as creating, maintaining, maintaining, even destroying. These particularities of Rera Wulan Tana Ekan are the basis for the importance of intense communication between humans and Rera Wulan Tana Ekan God’. Ri'e Hikun Liman Wanan ‘right hand corner of the house’ is a medium of human communication with Rera Wulan Tana Ekan ‘God’.